Pros and Cons Perspectives on the Amendment to Governor Regulation No. 5 of 2018 concerning the Implementation of Caning Law in Aceh - Niswah, Sayyidatin; Maharani, Yosie Graciela (Dinasti Research, 2025)
This study examines in depth the changes in the implementation of caning in Aceh following the issuance of Aceh Governor Regulation Number 5 of 2018, which shifted the location of caning from public places to correctional facilities. This change has become a controversial issue because it is considered to shift the values ​​of Islamic law that have long been the legal and cultural identity of the Acehnese people. Prior to this regulation, caning was carried out openly in front of the public, such as in mosque courtyards, with the aim of providing a deterrent effect and serving as a moral lesson for the community. However, after the enactment of the Governor Regulation, caning is carried out in prisons to maintain the dignity of the perpetrator, avoid psychological trauma, and prevent the spread of the convict's identity on social media. This study uses a descriptive qualitative method with a juridical-sociological approach, where data is obtained through interviews with residents in Lhokseumawe City and analysis of relevant legal documents. This approach not only examines the normative aspects of the regulation but also examines how these legal norms interact with the social reality of society. The results of the study indicate two main views in society: The pro-candidate group supports this change because it is considered more humane and in accordance with human rights principles, while the opposing group believes that implementing caning in public places is more effective in providing a deterrent effect and has educational and symbolic value in enforcing Islamic law. Overall, the changes in the implementation of caning in Aceh reflect an attempt to compromise between enforcing Islamic law and demands for legal modernization oriented towards humanitarian values. However, this policy still needs to be evaluated so that its implementation does not eliminate the meaning of Islamic law and the moral values ​​​​of Islamic law itself.